Effects of Adding Livestock and Poultry Manure to Field Strips of Straw on Soil Organic Carbon Components - Xinyu Zhao; Jiapeng Ji; Jinggui Wu (Applied Sciences)
This experiment takes typical chernozem soil as the research object to investigate the effects of adding various livestock and poultry manures during in situ strip composting of corn straw on the decomposition characteristics of the straw and the soil organic carbon content. This study set up a total of four treatments under the condition of following the equal carbon principle: (1) corn straw (T1); (2) corn straw + chicken manure (T2); (3) corn straw + cow dung (T3); (4) corn straw + decomposition agent (T4). The cumulative mass loss rate of straw in the treatment of adding livestock and poultry manure ranged from 51.60% to 54.33%, with a carbon release rate of 75.34% to 76.64%. Correlation analysis revealed a significant positive relationship between SOC, straw mass loss rate, and straw carbon release rate. Furthermore, there was a significant positive correlation between organic carbon components such as DOC, EOC, POC, and MBC with CPMI, while showing a significant negative correlation with the oxidation stability coefficient (KOS). Incorporating corn straw into livestock and poultry manure and returning it to the field in in situ strips effectively enhances the decomposition process of straw, leading to an increase in the organic carbon content of chernozem soil.